Thermal and Spectroscopic Studies of Transition Metal Complexes with Dihydrobis(2-Mercaptobenzothiazolyl)borate - Ahmad1, Naushad; Alam1, Manawwer; Kumar2, Parveen; Adil Hashmi2, Athar; Wahab3, Rizwan (Asian Journal of Chemistry, 2013)
The complexing behaviour of dihydrobis(2-mercaptobenzothiazolyl)borate towards the transition metal ions namely, Co(II), Ni(II) and Cu(II) have been examined by elemental analysis, magnetic susceptibility, thermal, conductivity and spectral studies viz. FT-IR, NMR, UV-VIS and ESI-MS. Spectroscopic results support a square planar geometry in Cu(II) complex, while an octahedral geometry is suggested in case of Co(II) and Ni(II) complexes. Thermal behaviour and kinetics of all compounds are investigated by thermogravimetric analysis. The TGA profile of borate anion and Cu(II) complex shows a single stage unlike that of two stage decomposition plot of the Co(II) and Ni(II) complexes. The evaluation of kinetic parameters (E, ln A, DH, DS and DG) of all thermal decomposition stages have been evaluated by graphical method using the equation of Coats-Redfern equation. The activation energy of Co(II), Ni(II) and Cu(II) complexes expected to increase in relation with decreasing in their radius. The molar conductance of these complexes shows a non-electrolyte behaviour.